Nominal Exchange Rate Dynamics for the Taka - FULLERTON, Thomas M.; BARAI, Dipanwita; WALKE, Adam G. (Turkish Economic Review, 2017)
Abstract. Error correction modeling is used to model the nominal exchange rate for the Bangladeshi taka. Based on existing trade volumes and trade practices, the bilateral exchange rate of the taka with the dollar is analyzed. Annual frequency data are utilized for the study. The sample data cover the four decade period from 1976 to 2015. Results indicate that a balance of payments modeling approach performs more reliably than a monetary balances approach. Keywords. Regional economics, Business cycles, Economic indicators. JEL. F31, O53.